HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA-TANGAN TERHADAP KEMAMPUAN LAY-UP SHOOTTIM BOLA BASKET PUTRA SMA NEGERI 1 PEKANBARU - Robby Septian Septian; Saripin '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problems in this research originated from the observation of the authors found deficiencies in the field of men’s basketball team SMAN 1 Pekanbaru n doing lay-up while match. Lay-up shoot technique while playing is still nor perfect, step and footstool during lay-up shoot ins not clear. Lay-up technique is not done with explosive maximum power of leg muscle, an not accompanied by a balanced motion coordination between the eye and the hand. So that the  ball is not on target. The purpose of this research was to determine the relationship between explosive power of leg muscle ang hand-eye coordination on the ability of the lay-up shoot of men’s basketball team SMAN 1 Pekanbaru. The population in this research is the men’s basketball team SMAN 1 Pekanbaru, which amounted to is people,using total sampling technique and all of the population being sampled. So, T test is not required. To obtained the data, this research using vertical jump test t determine the explosive power of leg muscle, using throw-catching a tennis ball test for eye-hand coordination and the ability to lay-up shoot. Data was analysis with simple product momentcorrelation. Based on the analysis of data, then obtained a correlation X1 with Y amunt rcount = 0,613> rtable = 0,532and X2withY amountrcount= 0,776> rtable = 0,532while X1 dan X2withY amount rcount= 0,80> rtable= 0,532 . Because of all the relationships shows in data analysis is significant. The hypothesis Ho was resected and hypothesis Ha be accepted. That is, thereis a relationship between the explosive power of leg muscle and eye-hand coordination against the ability to lay-up shoot of the men’s basketball team SMAN 1 Pekanbaru, with the provisions of the correlation of a variable with other variable determined from rcount> rtable. Key word : Exsplosive Power Of Leg Muscle,Eye-Hand Coordination,Ability to Lay-Up Shoot.